2019
DOI: 10.5194/isprs-archives-xlii-2-w18-99-2019
|View full text |Cite
|
Sign up to set email alerts
|

Investigation Into the Behaviour and Modelling of Chromatic Aberrations in Non-Metric Digital Cameras

Abstract: Abstract. Chromatic aberration in colour digital camera imagery can affect the accuracy of photogrammetric reconstruction. Both longitudinal and transverse chromatic aberrations can be effectively modelled by making separate measurements in each of the blue, green and red colour bands and performing a specialized self-calibrating bundle adjustment. This paper presents the results of an investigation with two aims. The first aim is to quantify the presence of chromatic aberration in two sets of cameras: the six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 9 publications
4
6
0
Order By: Relevance
“…The final adjustment used the constraint of the second adjustment as well as the constraints to enforce the equivalence of the principal point coordinates of the cameras corresponding to the three spectral bands. The third adjustment used by [26] is comparable to the adjustment used by [25,26], who concluded that ether common object points or alternatively, common object points with EOP constraints are needed.…”
Section: Related Workmentioning
confidence: 94%
See 4 more Smart Citations
“…The final adjustment used the constraint of the second adjustment as well as the constraints to enforce the equivalence of the principal point coordinates of the cameras corresponding to the three spectral bands. The third adjustment used by [26] is comparable to the adjustment used by [25,26], who concluded that ether common object points or alternatively, common object points with EOP constraints are needed.…”
Section: Related Workmentioning
confidence: 94%
“…In this paper, a similar method to [25,26] is used. In this section, the functional model and the add adjustment constraints will be introduced.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations